Assisting cultivation of photosynthetic microorganisms by microbial fuel cells to enhance nutrients recovery from wastewater. (August 2017) - Colombo, Alessandra; Marzorati, Stefania; Lucchini, Giorgio; Cristiani, Pierangela; Pant, Deepak; Schievano, Andrea
Graphical abstract: Highlights: MFC can assist photosynthetic microorganisms cultivation for wastewater treatment. Photosynthetic dissolved oxygen sustained cathodic reaction at comparable extent to air-cathode MFCs. Efficient removal from anodic chamber prevented COD leakage to the cathodic chamber. Cathode helped in consuming photosynthetic oxygen and increased pH in the bulk. Nutrients were recovered by electro-migration and diffusion to the cathodic chamber. Abstract: Spirulina was cultivated in cathodic compartments of photo-microbial fuel cells (P-MFC). Anodic compartments were fed with swine-farming wastewater, enriched with sodium acetate (2.34 gCOD  L −1 ). Photosynthetic oxygen generation rates were sufficient to sustain cathodic oxygen reduction, significantly improving P-MFC electrochemical performances, as compared to water-cathode control experiments. Power densities (0.8–1 W m −2 ) approached those of air-cathode MFCs, run as control. COD was efficiently removed and only negligible fractions leaked to the cathodic chamber. Spirulina growth rates were comparable to those of control (MFC-free) cultures, while pH was significantly (0.5–1 unit) higher in P-MFCs, due to cathodic reactions. Alkaliphilic photosynthetic microorganisms like Spirulina might take advantage of these selective conditions. Electro-migration along with diffusion to the cathodic compartment concurred for the recovery of most nutrients. Only P and Mg were retained in the anodic chamber. A deeper look into electro-osmotic mechanisms should be addressed in future studies.